2020
DOI: 10.1088/1361-6528/ab7c4a
|View full text |Cite
|
Sign up to set email alerts
|

Perceptible exciton-to-trion conversion and signature of defect mediated vibronic modes and spin relaxation in nanoscale WS2 exposed to γ-rays

Abstract: In this work, we report manifested optical, optoelectronic and spin–spin relaxation features of a few layered tungsten disulphide (WS2) nanosheets subjected to energetic γ-photons (∼1.3 MeV) emitted from a Co60 source. Upon intense irradiation (dose = 96 kGy), a slight departure from the pure hexagonal phase was realized with the introduction of the trigonal phase at large. Moreover, in the Raman spectra, as a consequence of the radiation-induced effect, an apparent improvement of the E-to-A mode intensity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
5
10
0
Order By: Relevance
“…In our investigation, DT A exhibited the red-shift peak energy behavior similar to the trion case. Moreover, increasing excitation intensity beyond the neutral-to-trion conversion exhibits diminishing neutral exciton and increasing trion intensities (at a high screening region) as observed previously. ,, A similar behavior was observed in DT A , as shown in Figure d,e. This observation enabled us to conclusively determine the DT A nature as the defect-induced trion state (distinct from the neutral state).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In our investigation, DT A exhibited the red-shift peak energy behavior similar to the trion case. Moreover, increasing excitation intensity beyond the neutral-to-trion conversion exhibits diminishing neutral exciton and increasing trion intensities (at a high screening region) as observed previously. ,, A similar behavior was observed in DT A , as shown in Figure d,e. This observation enabled us to conclusively determine the DT A nature as the defect-induced trion state (distinct from the neutral state).…”
Section: Resultssupporting
confidence: 85%
“…Consequently, the A 0 energy keeps increasing by the band-filling effect with a negligible carrier screening effect. Similar phenomena were also observed in trions (Figure a–c) with a more prominent carrier screening effect due to conversion from neutron excitons to trions at high excitation intensity (Figure d–f). , The slope of the T A peak was much steeper in region II than region I owing to high carrier screening, as observed before. , Furthermore, T A peak intensity became higher than A 0 in region II due to the neutral exciton-to-trion conversion (schematically shown in Figure d inset). , Moreover, the trion peak energies gradually decreased with a slope (in region I) of approximately 6.1 × 10 –3 in Re-WS 2 /SiO 2 , much higher than the WS 2 /SiO 2 sample (2.2 × 10 –3 shown in Figure a,b). This observation suggested an enhancement of the carrier screening effect due to Re-doping in the Re-WS 2 /SiO 2 sample.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, in a study reported by Sarmah et al, a γ irradiation dose of 96 kGy on exfoliated nanoscale WS 2 transitioned its structural symmetry from the 2H to 1T phase and also induced n-type doping. 14 In one study reported by Elafandi et al, the radiation hardness of monolayer WS 2 and WSe 2 was investigated under a γ irradiation dose up to 560 kGy and they are presented as potential materials for space and nuclear science applications. 15 Felix et al reported changes in the magnetic phase from diamagnetic to ferromagnetic and enhancement in the p-type doping in monolayer WS 2 after 400 Gy irradiation.…”
Section: Introductionmentioning
confidence: 99%